PENGUKURAN SENSITIVITI KEPELBAGAIAN BUDAYA DALAM KALANGAN GURU MENGGUNAKAN MODEL DMIS (DEVELOPMENTAL MODEL OF INTERCULTURAL SENSITIVITY) OLEH BENNETT - Omar, Hafzan; Haron, Zolkepeli (Journal of Techno-Social, 2018)
The Malaysian community is multiethnic that is born of cultural diversity. This diversity if not properly managed will create social tensions and conflicts that will affect the harmony and security of the country. The state education system is a tool for realizing unity and teacher is an important change agent in school. The sensitivities of cultural diversity among teachers need to be measured to see the teacher’s sensitivity to the diversity inherent in teachers and pupils. This concept paper discusses the concept of cultural diversity among Malaysian teachers and the DMIS Model (Developmental Model of Intercultural Sensitivity). The DMIS model produced by Bennett can explain the level of sensitivity of cultural diversity. This model contains 6 levels of denial, defense and reduction that fall into the ethnocentrism stage, while acceptance, adaptation and integration are classified as ethnorelative. Individuals with ethnorelative orientation will be more sensitive to cultural differences while individuals less sensitive to cultural differences have ethnocentric orientations. This DMIS model will show the level of sensitivity of teachers to be either ethnorelative or ethnocentric.